Practices of growth assessment in children: Is anthropometric measurement important? - Jose RL Batubara (Indonesian Pediatric Society Publishing House, 2016)
Assessing and monitoring growth is common practice in pediatric care, and health professionals accept routine growth monitoring in children as a standard component of community child health services throughout the world. In clinical level, by these activities one can detect and intervene while growth faltering happens. The internationally recommended way to assess malnutrition at population level is to take anthropometric measurements. In developed countries, growth monitoring is an intrinsic part of 'well child' clinics. As growth is a proxy for child health, the child who grows well is generally healthy and illness in a child is usually associated with poor growth. Interpretation of child growth is based on anthropometric indicators established in a reference population with cut-off points to differentiate under- and overnutrition, short stature or tall stature, proportionate or disproportionate growth. Practices of growth monitoring consist of regularly measuring the weight and height of children, then plotting the information on a growth chart to make abnormal growth visible. When growth is abnormal, the health worker does something in concert with the family and as a result of these actions the child receives appropriate social or medical support, his or her nutrition improves, or a serious condition is diagnosed earlier.